The Construction of Space in English and German Literature 1790–1848: Geoparsing the Corvey Collection - Nivala Asko (United Kingdom, 2025)
In this article, I analyse named entity linking as a new method to study the construction of space in the English and German texts of European Literature, 1790–1840: The Corvey Collection. The Corvey Collection is among the most comprehensive datasets to have survived from the Romantic Era of literature. However, German-language documents in particular suffer from poor OCR scanning. To avoid noise caused by incorrectly digitized characters, I have re-OCRed the collection. In contrast to named entity recognition, named entity linking is able to disambiguate toponyms and find coordinates for them from linked open data sources such as DBpedia. I have then imported the geocoded places to geographic information systems, which enables comparing spaces imagined in British and German literature from the 1790s to the 1840s. To link spatial information to the semantic content of texts, I have applied topic modeling to find common themes shared by the works. Studying the spatial imagination of the popular texts published in the Romantic era discloses an alternative view to our present notion of Romanticism based on the close reading of a few canonized authors. The comparison of English and German corpora shows the way in which the spatial imagination reflected the asymmetrical relationship of center and periphery: the core of British literature was located in London, whereas no single center appears in the German-language data.